How do you solve ln(x^2-x+1)-ln(x-1)+ln(x^2-1)=ln9? Precalculus Solving Exponential and Logarithmic Equations Logarithmic Models 1 Answer cspark1981 Nov 1, 2015 x = 2 Explanation: ln A + ln B = ln (AB) ln A - ln B = ln (A/B) ln (x^2-x+1) - ln (x−1) + ln (x^2−1) = ln 9 ln (((x^2-x+1)(x^2−1))/(x−1)) = ln 9 ln (((x^2-x+1)(x−1)(x+1))/(x−1)) = ln 9 (x^2-x+1)(x+1) = 9 x^3 = 8 x = 2 Answer link Related questions What is a logarithmic model? How do I use a logarithmic model to solve applications? What is the advantage of a logarithmic model? How does the Richter scale measure magnitude? What is the range of the Richter scale? How do you solve 9^(x-4)=81? How do you solve logx+log(x+15)=2? How do you solve the equation 2 log4(x + 7)-log4(16) = 2? How do you solve 2 log x^4 = 16? How do you solve 2+log_3(2x+5)-log_3x=4? See all questions in Logarithmic Models Impact of this question 1574 views around the world You can reuse this answer Creative Commons License